PENERAPAN MODEL PEMBELAJARAN ACTIVE LEARNING TIPE QUIZ TEAM TERHADAP HASIL BELAJAR SISWA (Penelitian Eksperimen Quasi Pada Mata Pelajaran Ekonomi Kelas X di SMA Negeri 1 Gegesik Kabupaten Cirebon) - Poy Saefullah Zevender (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2021)
One of the main problems in formal learning is the low absorption of students because the learning process is still using the conventional model. The expected goal and contained in this study is to find out how students respond to economics subjects with the application of the quiz team type active learning learning model, to find out whether there are differences in learning outcomes in economics subjects between students who use or get the application of the quiz team type of active learning learning model and students who do not use or get the application of the quiz team type of active learning learning model, to find out whether the application of the quiz type of active learning learning model team influence on student learning outcomes in economic subjects. The research that the author has used is quasi-experimental. While the approach method that the author uses in this study is an experimental approach or a comparative approach, because in this study, the authors compare between two classes, one class using the application of an active learning learning model and the other using a conventional learning model. The results showed that there was an effect of the active learning model on student learning outcomes. This is evidenced by the average final test scores obtained from the two groups, namely 79.12 for the experimental class and 70.35 for the control class. To see the magnitude of the effect, the R Square value of 0.626 means that active learning learning type quiz team has a positive effect of 67% on student learning outcomes. Thus, it can be concluded that economic learning with the application of the quiz team type of active learning learning model can effectively improve student learning outcomes. Keywords: quasi-experimental research, active learning model type quiz team, learning outcomes.